Effective fragment potential study of the influence of hydration on the vibrational spectrum of glucose - Vrančić, Christian; Petrich, Wolfgang (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2011)
The standard agent glucose has been the subject of numerous experimental and theoretical studies, especially in the aqueous environments which are present in most biochemical processes. The impact of the solvation process on the vibrational spectra of glucose in the mid-infrared region is investigated in this work. The computational study focused both on the variation of the number of surrounding water molecules from 0 to 229 and on the number of single spectra included in the iterative averaging process. The calculations consisted of a combination of force field methods for the sampling of the configuration space and density functional theory for further geometry optimizations. Effective fragment potentials (EFPs) were employed for the description of the solvent as a compromise between accuracy and computational complexity. A correlation between the experimental data and the number of surrounding water molecules could not be observed for an averaging over a small set of computed single spectra. The inclusion of an additionial polarizable continuum model (PCM) also showed no further impact. However, an increase in the number of underlying single spectra in the averaging process increased the correlation between simulations and the experiment substantially. Especially for 18 explicit EFP water molecules, an inclusion of 80 single spectra delivered a Pearson’s correlation coefficient r ≈ 0.94.